Computer Networking / A Top-Down Approach Featuring the Internet - Kurose, James F.; Ross, Keith W., 1956- (Pearson Addison-Wesley, 2004)
This book provides a top-down approach to this study by beginning with application-level protocols and then working down the protocol stack. Computer Networks and the Internet, Application Layer, Transport Layer, The Network Layer, The Link Layer and Local Area Networks, Wireless and Mobile Networks, Multimedia Networking, Security in Computer Networks, Network Management, References, Index.